SOME PSYCHO-PEDAGOGICAL CONSIDERATIONS ON MUSICAL EDUCATION - Călin DRAGOŞ (Studia Universitatis Babeş-Bolyai. Musica)
Nowadays, the educational system faces multiple challenges regarding pupils’ education, whether socio-human or professional education. Music education is the oldest component of Romanian pedagogy, highlighting values which have been structured throughout the years and represent not only cultural and historical facts, but the elements of a world outlook. It is then compulsory to present the real, correct aesthetic education within the educational system. Music teaching has had serious, acknowledged impact on artistic, humanistic, moral, civic, intellectual education. The importance of these aspects requires broader historical and cultural investigation. The full pedagogical and ethical meaning of meta-knowledge is developed in a didactic and epistemological context. As a means to acquire knowledge and strategies for success, meta-knowledge is a factor in pupils’ identification within their culture. It is used in relationship with the other, by producing a set of knowledge research and knowledge building. In this way, students can progress from music consumers to music users and producers, knowledge and aesthetic taste gatherers who strive for ideals and beauty.